The Relationship Between Ambivalence Over Emotional Expression and Impulsivity With the Mediating Role of Self-Compassion in Adolescents With Depressive Disorder - Zanjanchi Nikoo, Saeed; Farahani, Ali (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the mediating role of self-compassion in the relationship between ambivalence over emotional expression and impulsivity in adolescent students diagnosed with depressive disorder. Methods and Materials: The research employed a descriptive-correlational design based on structural equation modeling (SEM). The statistical population included male adolescents in lower and upper secondary schools in Qazvin City during the 2024 academic year, all of whom were referred to the city’s Educational Counseling Center and clinically diagnosed with depressive disorder. A sample of 150 students was selected through convenience sampling. Data were collected using the Beck Depression Inventory (BDI), the Barratt Impulsiveness Scale (BIS), the Emotional Expressivity Questionnaire (EEQ), and the Self-Compassion Scale (SCS). Descriptive statistics, Pearson correlation, path analysis, and bootstrapping were used to analyze the data through SPSS version 26 and AMOS. Findings: Correlation analysis revealed a significant positive relationship between ambivalence over emotional expression and impulsivity, and a significant negative relationship between self-compassion and impulsivity (p < .01). Path analysis confirmed that self-compassion significantly mediates the relationship between ambivalence over emotional expression and impulsivity. Model fit indices (e.g., RMSEA = 0.070, CFI = 0.913, GFI = 0.910) indicated an acceptable model fit. Bootstrapping further verified the significance of the indirect effect (standardized indirect effect = 0.273, p = .01), confirming the mediating role of self-compassion. Conclusion: Higher self-compassion is associated with lower impulsivity and reduced emotional ambivalence, suggesting that interventions aimed at enhancing self-compassion could help mitigate maladaptive emotional and behavioral responses in this population.